Needs analysis for an ESP case study developed for the context-aware ubiquitous learning environment. (25th July 2018) - Chen, Yi-Wen; Liu, Gi-Zen; Lin, Vivien; Wang, Hong-You
Abstract: The integration of context-aware ubiquitous learning (CAUL) into English for Specific Purposes (ESP) learning has become increasingly widespread due to the enhanced interaction between learners and situated contexts. Using an authentic learning site on environmental protection and its related discourse-specific English as target knowledge, this study analyzed the learning needs for developing ESP knowledge and skills through the use of smartphones and QR codes. Different need choices of the four language skills, requirements of CAUL system design, and effective audio–visual materials for social interaction are discussed. Based on previous reviewed arguments and current empirical arguments, the quantitative results reveal significant findings in ESP material design, content knowledge, and effective methods for CAUL. Further, qualitative interview results are classified into technological viewpoints and practical infield viewpoints. Consequently, identified themes and contradictions among three target groups—experts, students, and guides—are explained in terms of different pursuits of context-specific English learning needs.